COMPILATION OF ACTIVE FAULT DATA IN PORTUGAL FOR USE IN SEISMIC HAZARD ANALYSIS - Nemser, E.S. (2010)
To estimate where future earthquakes are likely to occur, it is essential to combine information about past earthquakes with knowledge about the location and seismogenic properties of active faults. For this reason, robust probabilistic seismic hazard analysis (PSHA) integrates seismicity and active fault data. Existing seismic hazard assessments for Portugal rely exclusively on seismicity data and do not incorporate data on active faults. Project SHARE (Seismic Hazard Harmonization in Europe) is an EC-funded initiative (FP7) that aims to evaluate European seismic hazards using an integrated, standardized approach. In the context of SHARE, we are developing a fully-parameterized active fault database for Portugal that incorporates existing compilations, updated according to the most recent publications. The seismogenic source model derived for SHARE will be the first model for Portugal to include fault data and follow an internationally standardized approach. This model can be used to improve both seismic hazard and risk analyses and will be combined with the Spanish database for use in Iberian- and European-scale assessments.